Halal agriculture as an effort to strengthen the global halal value chain in order to increase international trade - Mutmainah, Siti; Romadhon, Muhammad Ryan (Journal of Islamic Economics Lariba, 2023)
IntroductionIndonesia as an agricultural country with a Muslim-majority society has great potential to develop halal agriculture. The halal agricultural sector must be strengthened so that agricultural products can be exported abroad.ObjectivesThe purpose of this study is to strengthen the global halal value chain to increase international trade through the halal agriculture sector. MethodThis study employed qualitative methods using a descriptive approach. The data collection method used literature studies from various reference journals, agency reports, and online media.ResultsThis research concludes that the development of halal agriculture has great potential for development in Indonesia, so that it can increase international trade by improving the global halal value chain. With the development of halal agriculture in Indonesia, it is expected to be able to bring Indonesia to become a country with food security and the center of the halal industry in the world. ImplicationsThe results of this study can be guidelines for policymakers to improve contribution of halal agriculture in Indonesian export. Furthermore, it can contribute to further studies in global halal value chain for agriculture-based products.Originality/NoveltyThis study contributes to body of knowledge of global halal value chain with emphasize on agricultural sector in Indonesia.